2010
DOI: 10.4081/ijas.2010.e56
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ghrelin mRNA level, plasma growth hormone concentration and performance in different dietary energy and protein levels in broiler chicken

Abstract: We studied the effects of different energy and protein contents of the diet on performance, growth hormone concentration and ghrelin gene expression in broiler chicken. Two experiments were conducted to determine whether different dietary energy and protein levels alter growth hormone concentration and ghrelin mRNA abundance in broiler chicks. Body weight and feed intake were recorded weekly. Blood, carcass traits and proventriculus samples were collected at 21, 42 and 56 days of age. Blood samples assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
5
2
Order By: Relevance
“…As already pointed out, ghrelin is mainly considered as a "hunger signal" in chicken, similar to its function in mammalian systems (Kaiya et al, 2007. This function is referred to the endogenous ghrelin (Kaiya et al, , 2007 and is possibly not connected with the peripherally administered exogenous ghrelin that was applied in the present study.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…As already pointed out, ghrelin is mainly considered as a "hunger signal" in chicken, similar to its function in mammalian systems (Kaiya et al, 2007. This function is referred to the endogenous ghrelin (Kaiya et al, , 2007 and is possibly not connected with the peripherally administered exogenous ghrelin that was applied in the present study.…”
Section: Discussionmentioning
confidence: 77%
“…As already pointed out, ghrelin is mainly considered as a "hunger signal" in chicken, similar to its function in mammalian systems (Kaiya et al, 2007. This function is referred to the endogenous ghrelin (Kaiya et al, , 2007 and is possibly not connected with the peripherally administered exogenous ghrelin that was applied in the present study. The administration of exogenous ghrelin has different effects on appetite or feed intake in chickens (Stimulation/No effect/Inhibition) as reviewed by Kaiya et al, (2013).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1 shows the lowest level of ghrelin expression in broiler chickens was in the treatment which only had tallow in their diet. Ghazanfari et al [25] stated in their research that ghrelin plasma concentration decreases when fat is included in the diet indicating that ghrelin secretion is sensitive to diet composition. Salehi et al [26] found that ghrelin secretion decreased when fat was included in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Research on animals was conducted in Rudsar, Iran (37.1378° N, 50.2836° E) and all the procedures used were approved by the Ethics Committee in Animal Use (Approval date: 10/05/2016; No: 10038). The experiment, in a completely randomized design with 6 treatments and 4 replicates using 240 1-day-old male chicks of strain Ross 308, was conducted in the starter period (1-10 day), grower period (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and finisher period (29-42). Each replication included 10 chicks.…”
Section: Chickens Diets and Managementmentioning
confidence: 99%